The amplitude of low frequency fluctuation and spontaneous brain activity alterations in age-related macular degeneration - Zhang, Yan Yan; Hu, Jin Yu; Ling, Qian; Xu, San Hua; Kang, Min; Wei, Hong; Zou, Jie; Yi, Quanyong; Tan, Gang; Shao, Yi (Frontiers in Medicine, 2025)
BackgroundWet age-related macular degeneration (wAMD) is a vision-threatening eye disease worldwide. The amplitude of low-frequency fluctuation (ALFF) method was used to observe changes in spontaneous brain activity, which may help to investigate the underlying pathological mechanism of AMD.MethodsEighteen patients with wAMD and 18 age- and gender-matched healthy controls (HCs) were recruited. The ALFF method was used on each subject and mean ALFF values were compared between groups. The receiver operating characteristic (ROC) curve was used to compare the two groups.ResultsALFF values in the temporal lobe and limbic lobe/parahippocampal gyrus were significantly higher than controls, while values in the postcentral gyrus were significantly lower. The under the curve of the ROC (AUC) of the three regions shows high accuracy of the diagnosis.ConclusionThe abnormal spontaneous brain activity of patients with AMD suggests scope for the use of ALFF in the diagnosis or prognosis in AMD.